IMPROVING THE STUDENTS’ READING SKILL THROUGH SHORT STORY TECHNIQUE - Noening Poejilestari (STIBA IEC JAKARTA, 2019)
The aims of this research are to solve the English reading problem and to know the effectiveness of using short story in teaching reading. This research is using classroom action research with three cycles. Each cycle consist of four steps; planning, action, observation and reflection. The sample of the research is the seventh grade of Junior High School students. The data are obtained from direct and indirect observation and collaboration. In the direct observation, the data is from field observation and In the indirect one, the data is from the test result. Based on the data collected it is found that some students are active in reading practice through short story technique. Further, the students have more desire and motivation to improve their reading skill. Looking up the evaluation table, the reading from thirty three students in three cycles can be explained; in the first cycle, students get the average score 63.0 or there are thirteen students (39.4%) who achieve the standard of minimum score achievement (65.0). In the second cycle, they get the average score 69.6 or there are twenty eight students (84.8%) who achieved the standard minimum score. While in the third cycle, they get 77.0 on their average sore or all of them (100%) can achieve the standard minimum score. Furthermore, the writer concludes that the use of short story technique approach can be one of the appropriate approach to teach English reading skill for the students